Bone Morphogenetic Protein 13 Has Protumorigenic Effects on Hepatocellular Carcinoma Cells In Vitro. - Kersten, Vanessa; Seitz, Tatjana; Sommer, Judith; Thasler, Wolfgang E.; Boßerhoff, Anja Katrin; Hellerbrand, Claus (International Journal of Molecular Sciences, 2023)
Activated hepatic stellate cells (HSCs) play a key role in hepatic fibrosis and, thus, build the "soil" for hepatocarcinogenesis. Furthermore, HSCs are known to promote the progression of hepatocellular carcinoma (HCC), but the molecular mechanisms are only incompletely understood. Recently, we newly described the expression of bone morphogenetic protein 13 (BMP13) by HSCs in fibrotic liver tissue. In addition, BMP13 has mostly been studied in the context of cartilage and bone repair, but not in liver disease or cancer. Thus, we aimed to analyze the expression and function of BMP13 in HCC. Expression analyses revealed high BMP13-expression in activated human HSCs, but not in human HCC-cell-lines. Furthermore, analysis of human HCC tissues showed a significant correlation between BMP13 and α-smooth muscle actin (α-SMA), and immunofluorescence staining confirmed the co-localization of BMP13 and α-SMA, indicating activated HSCs as the cellular source of BMP13 in HCC. Stimulation of HCC cells with recombinant BMP13 increased the expression of the inhibitors of differentiation 1 (ID1) and 2 (ID2), which are known targets of BMP-signaling and cell-cycle promotors. In line with this, BMP13-stimulation caused an induced SMAD 1/5/9 and extracellular signal-regulated kinase (ERK) phosphorylation, as well as reduced expression of cyclin-dependent kinase inhibitors 1A (CDKN1A) and 2A (CDKN2A). Furthermore, stimulation with recombinant BMP13 led to increased proliferation and colony size formation of HCC cells in clonogenicity assays. The protumorigenic effects of BMP13 on HCC cells were almost completely abrogated by the small molecule dorsomorphin 1 (DMH1), which selectively blocks the intracellular kinase domain of ALK2 and ALK3, indicating that BMP13 acts via these BMP type I receptors on HCC cells. In summary, this study newly identifies stroma-derived BMP13 as a potential new tumor promotor in HCC and indicates this secreted growth-factor as a possible novel therapeutic target in HCC.
EVALuna2:538506

Bone morphogenetic protein 13 in hepatic stellate cells and hepatic fibrosis - Peschl, Vanessa; Seitz, Tatjana; Sommer, Judith; Thasler, Wolfgang; Boßerhoff, Anja Katrin; Hellerbrand, Claus (Journal of Cellular Biochemistry, 2022)
Hepatic fibrosis can be considered as a deregulated wound healing process in response to chronic liver injury. Bone morphogenetic protein 13 (BMP13) has been described to promote bone and tendon repair. In this study, we aimed to analyze the expression and function of BMP13 in hepatic fibrosis. We found increased BMP13 expression during the activation of hepatic stellate cells (HSCs), which is known as the key event of hepatic fibrosis. Fitting to this, BMP13 was elevated in murine models of hepatic fibrosis, and immunofluorescence staining showed colocalization of BMP13 and α-smooth muscle actin (α-SMA), a marker for activated HSC, in cirrhotic human liver tissue. BMP13 depletion in activated human HSC reduced the phosphorylation of smad1/5/9 and the expression of the transcription factor inhibitor of differentiation 1 (ID1), a known BMP target gene and profibrogenic factor. Furthermore, BMP13-depletion led to reduced proliferation and downregulation of collagen I α1 (COL1A1) and α-SMA, and, interestingly, also reduced phosphorylation of extracellular signal-regulated kinases (ERK). Conversely, stimulation with recombinant BMP13 induced the phosphorylation of smad1/5/9 and ERK, as well as the proliferation and the expression of ID1, COL1A1, and α-SMA in HSCs. These stimulatory effects were inhibited by dorsomorphin 1, a small-molecule inhibitor of the BMP-type I receptors activin receptor-like kinase-2 and -3, which are both expressed by HSC. In summary, these data indicate increased BMP13 expression in hepatic fibrosis as a profibrogenic factor. Thus, this soluble growth factor might have the potential as a new fibrosis marker and antifibrogenic therapeutic target in patients with chronic liver disease.
CRIS-Team Scopus Importer:2022-04-29
Keywords: BMP13; hepatic stellate cells; liver fibrosis